One new genus of the family Gesneriaceae for the flora of Vietnam - Phuong, Vu Xuan (Academia Journal of Biology, 2014)
The genus Lagarosolen W. T. Wang (Gesneriaceae) was published in 1984 with 1 species L. hispidus W. T. Wang. In 1993, D. Fang & L. Zeng have introduced one new species L. intergrifolius D. Fang & L. Zeng. These specimens were collected in Yunnan and Quangxi provinces of China. The genus Lagarosolen was regarded as endemic of China. During the study of specimes and documents of Gesneriaceae of Vietnam, we have found that the genus Lagarosolen has distributed also in Vietnam, with 1 species L. hispidus W. T. Wang; the specimens were collected in the Chodon district, Baccan province. Thus, this genus and this species were new records for the flora of Vietnam.